2015
DOI: 10.1186/s12871-016-0234-x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden occurence of hypotension and bradycardia during greenlight laser transurethral resection of prostate: case report of two cases

Abstract: BackgroundGreenlight laser transurethral resection of prostate (TURP) is a standard surgical method used to treat patients with prostate gland enlargement, it is safe and effective.Case presentationWe report two cases of sudden occurence of hypotension and bradycardia during greenlight laser TURP. Two patients with benign prostatic hypertrophy were scheduled for greenlight laser TURP under spinal anesthesia. Hypotension and bradycardia were suddenly occurred during the operation. The blood gas analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They also assumed that a prostate procedure may induce a vagal reflex because the pelvic splanchnic nerves, which are parasympathetic nerves, run close to the apex of the prostate at the level of the membranous urethra. 17) The prostate was not manipulated directly in this patient, lower urinary tract manipulation with endoscopic instruments during ureteral stents placement might have affected pelvic splanchnic nerves around the prostate. So, the transurethral procedure might have increased parasympathetic activity and induced a cardiac vagal reflex.…”
Section: Discussionmentioning
confidence: 93%
“…They also assumed that a prostate procedure may induce a vagal reflex because the pelvic splanchnic nerves, which are parasympathetic nerves, run close to the apex of the prostate at the level of the membranous urethra. 17) The prostate was not manipulated directly in this patient, lower urinary tract manipulation with endoscopic instruments during ureteral stents placement might have affected pelvic splanchnic nerves around the prostate. So, the transurethral procedure might have increased parasympathetic activity and induced a cardiac vagal reflex.…”
Section: Discussionmentioning
confidence: 93%
“…For nickel-base super-alloy, Manonukul and Dunne [38] added the CPFEM concept to analyze the crack formation characteristic in LCF and HCF. For the same material, Guan et al [39] incorporated CPFEM and high-resolution digital image correlation technique to analyze the strain localization under fatigue. It is reported that for a wide range of parameters, the CPFEM can predict the material behavior very accurately.…”
Section: Crystal Plasticity Modelmentioning
confidence: 99%